2016
DOI: 10.16965/ijar.2016.169
|View full text |Cite
|
Sign up to set email alerts
|

Macro and Microscopic Characteristics of the Gastrointestinal Tract of the Cattle Egret (Bubulcus Ibis)

Abstract: Introduction: Cattle egret (Bubulcus ibis) is widely spread in Egypt and acts as a reservoir for many diseases. Few study described the anatomical and histological picture of its gastrointestinal tract which plays an important role in its nutrition habits in correlation to transmission of diseases. Materials and Methods:The present work was carried out on ten cattle egrets of different age and sex. After euthanized; five birds were subjected to normal dissection to study their gross anatomy by injection of 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 9 publications
18
14
0
Order By: Relevance
“…The tunica submucosa composed of connective tissue fibres. This agrees with Rodrigues, Oliveira, et al (), Zaher et al () and Hussein and Rezk (). The tunica musculosa consisted of thick inner circular layer and outer thin longitudinal layer of smooth muscle fibres, and this come in alignment with Abd El‐Aziz (), Rodrigues, Abreu, et al (), Zaher et al () and Hussein and Rezk ().…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The tunica submucosa composed of connective tissue fibres. This agrees with Rodrigues, Oliveira, et al (), Zaher et al () and Hussein and Rezk (). The tunica musculosa consisted of thick inner circular layer and outer thin longitudinal layer of smooth muscle fibres, and this come in alignment with Abd El‐Aziz (), Rodrigues, Abreu, et al (), Zaher et al () and Hussein and Rezk ().…”
Section: Discussionsupporting
confidence: 92%
“…The jejunal villi were longer than the duodenal villi, but the ileal villi appeared with different length, while Nasrin et al () reported that the jejunal and ileal villi were shorter than that found in the duodenum, and moreover, Kadhim, Zuki, Noordin, Babjee, and Zamri‐Saad () documented that the duodenal villi height was greater than the jejunal and ileal villi. At the bases of the villi, the intestinal crypts were present, and this coincide with that obtained by Hussein and Rezk (). Moreover, Illanes, Fertilio, Quijada, Leyton, and Verdugo (), Monteiro de Souza de Carvalho and de Souza () and Rodrigues, Oliveira, et al () recorded that the duodenal villi is longer that the jejunal villi, while the ileal villi appeared with variable length.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations